2015
DOI: 10.1007/s13277-015-3996-8
|View full text |Cite
|
Sign up to set email alerts
|

MiR-378 suppresses prostate cancer cell growth through downregulation of MAPK1 in vitro and in vivo

Abstract: Prostate cancer is one of the biggest health problems for the aging male. To the present, the roles of dysregulated microRNAs in prostate cancer are still unclear. Here, we evaluated the anti-proliferative role of miR-378 in prostate cancer. And, we found that the expression of miR-378 was significantly downregulated in clinical prostate cancer tissues. In vitro assay suggested that overexpression of miR-378-suppressed prostate cancer cell migration and invasion promoted cell apoptosis. Furthermore, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 22 publications
2
50
0
2
Order By: Relevance
“…Previous studies showed that miR-378 inhibits prostatic carcinoma cell proliferation 8 and enhanced apoptosis of cardiomyocytes by reduced signaling in the Akt cascade. 38 Additionally, miR-378-5p could suppress cell proliferation and promote cell apoptosis in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that miR-378 inhibits prostatic carcinoma cell proliferation 8 and enhanced apoptosis of cardiomyocytes by reduced signaling in the Akt cascade. 38 Additionally, miR-378-5p could suppress cell proliferation and promote cell apoptosis in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 Specifically, miR-378 can enhance tumor cell survival by repressing SuFu and Fus-1, 24 increase the transcriptional activity of MyoD in part by repressing MyoR, 13 promote BMP2-induced osteogenic differentiation, 17 and also regulate osteoblast differentiation by targeting GalNT-7 in MC3T3-E1 cells. 21 Previous studies also demonstrated that miR-378 suppressed cell migration and promoted cell apoptosis in prostate cancer 8 and increased the size of lipid droplets and the incorporation of acetate into triacylglycerol.…”
Section: Introductionmentioning
confidence: 94%
“…The MAPK pathway is well-known to be associated with tumor progression [9] and its upregulation is associated with prostate cancer too [10]. In fact, it has been shown that miR-378 which targets MAPK1 is down-regulated in PCa cells [11]. In addition it has been shown that the Her2/Raf-1/MAPK/AP-1 axis promotes castrate resistant prostate cancer [10].…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted by Bo Hu demonstrated that miR‐212‐3p has an antitumour role in PCa by means of targeting MAPK1. MAPK1, which belongs to the MAPK family, is closely associated with PCa, especially in the aspects of cell proliferation, cell cycle and apoptosis . Ji‐ping Zeng demonstrated that miR‐212‐3p suppressed GC growth by modulating P21 CIP1 and P27 kip1 .…”
Section: The Role Of Mir‐212 In Cancermentioning
confidence: 99%
“…MAPK1, which belongs to the MAPK family, is closely associated with PCa, especially in the aspects of cell proliferation, cell cycle and apoptosis. 38 Ji-ping Zeng demonstrated that miR-212-3p suppressed GC growth by modulating P21 CIP1 and P27 kip1 . 39 It was verified that P21 CIP1 and P27 kip1 are associated with cell cycle arrest, and they showed a tendency for lower expression in GC.…”
Section: Mir-212 and The Cell Cyclementioning
confidence: 99%